Studies On ITT: Innovation and Technology Transfer - Sergio Baragetti (Current Approaches in Science and Technology Research Vol. 10, 2021)
In this chapter we discuss the role of Innovation and Technology Transfer in our complex and multidisciplinary world of science and engineering. Some considerations on the role of Universities, Research Centres, Public Institutions, Financial Institutions and Enterprises will be developed.